Evaluation of cocoa (Theobroma cacao L.) genotypes for pod and bean characters - Vithya, K; Balakrishnan, S; Jegadeeswari, V; Jeyakumar, P (Journal of Plantation Crops, 2018)
Performance of cocoa genotypes was studied for pod and bean characters at Pollachi, Coimbatore district. Based on the continuous evaluation, ten plus trees were identified as best performers. To study the stability of these genotypes, the pod and bean characters were evaluated during 2017-2018. Five uniformly ripened pods were collected from each genotype for the assessment of pod and bean characters. Cocoa genotypes used for the evaluation were TNAUCC 1-10. These genotypes differed from each other. Data were collected for number of flowers per tree, number of pods per tree, pod weight, pod set percentage, number of beans per pod, dry bean weight per pod, single dry bean weight and estimated dry bean yield per tree. The coefficient of variation in these genotypes differed from 5.7 per cent to 17.8 per cent. Number of pods per tree and pod set percentage was found to be high in TNAUCC 2. Pod weight, single dry bean weight, dry bean weight per pod and estimated dry bean yield per tree was maximum in TNAUCC 5. Number of pods per tree showed significant and positive correlation with pod weight, single dry bean weight and estimated dry bean yield per tree. Single dry bean weight had significant and positive correlation with dry bean weight per pod and estimated dry bean yield per tree. Hence, the cocoa genotypes TNAUCC 5 and TNAUCC 2 can be further exploited for crop improvement program.